2002
DOI: 10.1161/hc0302.102594
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Preference for Short Chain Fatty Acid Oxidation During Coronary Artery Constriction

Abstract: Background-Reduced fatty acid oxidation in hypoperfused myocardium is believed to result from impaired oxidation in mitochondria. This study suggests another mechanism, that oxidative capacity exceeds regulated entry of long chain fatty acid (LCFA). The ability of myocardium to oxidize fatty acids and metabolize glucose during stenosis was examined in open chest, anesthetized pigs. Methods and Results-The left anterior descending (LAD) coronary artery was infused for 40 minutes (5 mL/min LAD) with [2-13 C] but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…112,113,117,119124 Coronary artery infusion of saline solution containing 13 C-enriched fats or carbohydrates allows precise measurements of cardiac substrate utilization in the open-chest animal model, and more recently in the conscious, closed-chest pig model that is fully instrumented. 113,120 However, by definition, metabolic flux rates require multiple time points and therefore multiple sets of NMR spectra.…”
Section: C Mrs (Nmr)mentioning
confidence: 99%
“…112,113,117,119124 Coronary artery infusion of saline solution containing 13 C-enriched fats or carbohydrates allows precise measurements of cardiac substrate utilization in the open-chest animal model, and more recently in the conscious, closed-chest pig model that is fully instrumented. 113,120 However, by definition, metabolic flux rates require multiple time points and therefore multiple sets of NMR spectra.…”
Section: C Mrs (Nmr)mentioning
confidence: 99%
“…They speculated that this represented a protective mechanism that minimizes energy demand during low-flow ischemia. Although the intracellular signaling pathway responsible for this change in calcium kinetics is unclear, Lewandowski et al (13) have reported that metabolic responses in the mitochondrial oxidative pathways also respond to signals other than changes in oxygen delivery and tissue blood flow. These authors reported that in open-chest swine, myocardium perfused with a coronary stenosis preferentially oxidized short-chain fatty acids over endogenous longchain fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that Akt may inhibit fatty acid oxidation through inhibition of PPAR-a/PCG-1-dependent transcription [98] [99]. Increased oxidation of glucose and lactate through activation of the pyruvate dehydrogenase complex (PDC) may, in turn, enhance contractile function in the setting of ischemia [100]. The anti-apoptotic effect of insulin therapy may also be explained through its effect on preserving the pro-apoptotic peptide BAD in an inactive form [91].…”
Section: Metabolic Features Of Programed Cell Survivalmentioning
confidence: 99%